Can we improve adherence to guidelines for the treatment of lower urinary tract infection? A simple, multifaceted intervention in out-of-hours services - Henríquez, R. (2017)
Objectives: To improve antimicrobial prescribing behaviour of general practitioners in large-scale out-of-hours services for uncomplicated lower urinary tract infection (LUTI) in females aged 20-80 years, which is regarded as one of the most prevalent bacterial infections in primary care. Methods: A quasi-experimental design was used in two regional large-scale out-of-hours services. A simple, multifaceted intervention was offered in a 16 week period in one region (the intervention region). During the two washout periods, at 5 and 17 months, we observed diagnoses and prescriptions. The main outcome measure was the share of appropriate and inappropriate prescriptions. Results: The proportion of patients with LUTI ranged from 1.0% to 2.1%. The relative proportion of appropriate prescriptions in the intervention region increased from 26.9% to 69.4%, but decreased afterwards to 40.8%. Conclusions: A simple, multifaceted intervention for treatment of LUTI during out-of-hours care may improve the quality of antimicrobial prescribing, although the improvement may not be sustained in the longer term. © The Author 2012. Published by Oxford University Press on behalf of the British Society for Antimicrobial Chemotherapy. All rights reserved.